Respon Pertumbuhan dan Hasil Tanaman Kacang Tanah (Arachis hypogaea L.) akibat Pemberian Pupuk Organik Cair dan Jarak Tanam - Lia Amalia; Nunung Sondari; Nana Supriatna; Reni Nurhayatini; Agus Surya Mulya; Nendah Siti Permana (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
Peanut production has decreased, among others, due to cultivation techniques, varieties, diseases and increasingly narrow planting areas. One of the cultivation techniques to increase crop yields is the use of liquid organic fertilizer (POC) and spacing. The research method used was Randomized Block Design, factorial pattern. Consisting of two treatment factors, namely POC concentration (0, 5, 10, and 15 ml L-1 water) and spacing (30 cm x 10 cm, 30 cm x 15 cm and 30 cm x 20 cm), repeated three times. .. The results showed that: (1) there was an interaction between POC treatment and plant spacing on the number of pithy seeds and dry seed weight per plot. Independently, liquid organic fertilizer and plant spacing had an effect on plant height, number of leaves, dry weight of stover, number of filled pods, number of empty pods, percentage of filled pods and weight of 100 seeds, and (2) At a spacing of 30 cm x 15 cm, The optimum POC concentration was 13.24 ml L-1 of water, with a maximum dry seed weight of 1.436 kg plot-1 or equivalent to 2.66 tons ha-1.